0° vs. 180° CT localiser: The effect of vertical off‐centring, phantom positioning and tube voltage on dose optimisation in multidetector computed tomography. Issue 1 (17th August 2021) - Al‐Hayek, Yazan; Zheng, Xiaoming; Davidson, Rob; Hayre, Christopher; Al‐Mousa, Dana; Finlay, Campbell; Spuur, Kelly
Abstract: Introduction: Patient positioning is an essential consideration for the optimisation of radiation dose during CT examinations. The study objectives seek to explore the effects of vertical off‐centring, localiser direction (0° and 180°), and phantom positioning (supine and prone) on radiation dose, using three different tube voltages in multidetector computed tomography (MDCT) imaging. Methods: The trunk of a PBU‐60 anthropomorphic phantom was imaged using a Discovery CT750 HD – 128 slice (GE Healthcare). Images employing 0° and 180° localisers were acquired in supine and prone orientation for each combination of vertical off‐centring (±100, ±60 and ±30 mm) and different tube voltages (80, 120 and 140 kVp), using the system's automatic tube current modulation (ATCM) function. The displayed volume CT dose index (CTDIvol ) and dose length product (DLP) were recorded. Results: With incremental table off‐centring of ±100 mm, the dose at 120 kVp in the supine position ranged from 63% to 196% (0° localiser) and from 66% to 191% (180° localiser) as compared to iso‐centre. While in the prone position, the dose ranged from 62% to 195% (0° localiser); and 62% to 193% (180° localiser), with a notable dose increase at higher tube voltages. Dose variation and vertical off‐centring showed a significant relationship for both 0° and 180° localisers ( r  = 0.94 and 0.96, respectively, P  < 0.001). The CTDIvol variation between supine and prone phantom positions at ±100 mm off‐centring was 0.22 mGy (2.9%), and 0.19 mGy (2.3%) when the 0° and 180 ° localisers were utilised, respectively. Conclusions: Phantom off‐centring and localiser direction evidenced large dose variation. It is recommended that the 0° localiser is employed during CT examinations, in order to minimise the potential additional radiation dose which may result from off‐centring and the use of lower tube voltages where clinically appropriate. Abstract : Phantom off‐centring and localiser direction evidenced large dose variation. The authors recommend the acquisition of a 0° localiser, to reduce the increase in the total organ doses resultant from patient off‐centring or the dedicated use of automated positioning tools such as a 3D camera.